Diversitas Protista Pada Perairan Air Payau - Riska Agnesia (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
This review aims to determine the diversity of protists in brackish waters, the methodologies of several researchers, and compare the results obtained from various researchers. Some examples of locations and ecosystem types where protists were discovered include mangrove forests, coastal areas, swamps, aquaculture ponds, and river estuaries. Most journals conducted field research for identification and diversity analysis. However, some used DNA metabarcoding techniques for taxonomic and functional analysis, as well as comprehensive literature reviews. The results showed that the majority of protists discovered were animal-like protists (protozoa) and plant-like protists (algae), as well as plankton communities such as phytoplankton and zooplankton. The research results can be used a learning resource, demonstrating and educational aspect.